2018
DOI: 10.1039/c8an00093j
|View full text |Cite
|
Sign up to set email alerts
|

Estimating and correcting interference fringes in infrared spectra in infrared hyperspectral imaging

Abstract: Short-term acclimation response of individual cells of Thalassiosira weissflogii was monitored by Synchrotron FTIR imaging over the span of 75 minutes. The cells, collected from batch cultures, were maintained in a constant flow of medium, at an irradiance of 120 μmol m-2 s-1 and at 20 °C. Multiple internal reflections due to the micro fluidic channel were modeled, and showed that fringes are additive sinusoids to the pure absorption of the other components of the system. Preprocessing of the hyperspectral cub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
(49 reference statements)
2
16
0
Order By: Relevance
“…This strategy is therefore proposed as a step in the Fringe EMSC algorithm. In the Fringe EMSC algorithm proposed by Azarfar et al [16], they suggest to use multiple iterations. However, by selecting frequencies from multiple maxima in the Fourier domain, we experience that an iterative approach is not needed.…”
Section: Methods For a More Precise Fringe Signal Estimation (Simulation Study)mentioning
confidence: 99%
See 4 more Smart Citations
“…This strategy is therefore proposed as a step in the Fringe EMSC algorithm. In the Fringe EMSC algorithm proposed by Azarfar et al [16], they suggest to use multiple iterations. However, by selecting frequencies from multiple maxima in the Fourier domain, we experience that an iterative approach is not needed.…”
Section: Methods For a More Precise Fringe Signal Estimation (Simulation Study)mentioning
confidence: 99%
“…From the Fourier transform of this region, shown as inserted panels in Figure 7 (mean centering, windowing and zero-padding is applied), the two frequencies are present as two broad local maxima. In order to capture both frequency components of the signal, we propose to include two neighboring frequencies around a number n maxima local maxima, instead of including a portion of the frequencies with the highest amplitude, as suggested by Azarfar et al [16] The effects of including different sets of frequencies are shown in Figure 7, where the sets of selected frequencies are highlighted in the inserted panels. The corresponding corrected spectra are shown in Figure 7, where the frame color matches the color of the corrected spectrum.…”
Section: Methods For Selecting Multiple Frequency Maxima In the Fourier Domain (Experimental Data)mentioning
confidence: 99%
See 3 more Smart Citations